Implementasi Model Pembelajaran Teams Games Tournament untuk Meningkatkan Hasil Belajar Kognitif PKn Siswa Kelas V SD - Usman, Usman (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2023)
This study aims to improve the cognitive learning outcomes of Civics students in class V SD Negeri 3 Rarang Selatan, Terara District, East Lombok Regency for the 2017/2018 academic year, using a cooperative learning model of the Teams Games Tournament (TGT) type. This type of research is Classroom Action Research (CAR), with the research subject being fifth grade students of SD Negeri 3 Rarang Selatan, totaling 38 students, namely 25 male students and 13 female students. The research approach used is a qualitative and quantitative approach. The research design uses a research model from Kemmis & Mc. Taggart. Data collection techniques using observation sheets (observations) and tests. The data analysis technique used is the observation sheet of lesson plan implementation and cognitive learning outcomes tests. Based on the results of the study, it was found that the cognitive learning outcomes of students increased from cycle I to cycle II. At the end of cycle I as many as 20 students (52.63%) achieved learning completeness, while the final results of cycle II 31 students achieved learning mastery of (81.58%). From cycle I to cycle II there was an increase in achievement value of (28.95%). Thus it can be concluded that by applying the Teams Games Tournament (TGT) learning model it can improve the cognitive learning outcomes of Class V students at SD Negeri 3 Rarang Selatan for the 2017/2018 Academic Year, especially in organization material.